2015
DOI: 10.1002/2015gl064915
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the dominant ULF wave mode and generation mechanism for obliquely propagating waves in the Earth's foreshock

Abstract: We discuss mechanisms of the generation of ultralow frequency (ULF) upstream waves in the terrestrial foreshock that are essential for the acceleration of ions in space plasmas. The analysis is based on global hybrid kinetic simulations of the magnetosphere that provide realistic environment for the growth of the ULF waves in a quasi‐radial configuration of the interplanetary magnetic field. We focus on a long‐debated problem of the generation mechanism of oblique and parallel ULF waves and provide quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The majority of the ULF waves are either Alfvénic (mostly transverse) or magnetosonic-whistler (mostly compressive). We should also note that observed wave properties have also been reproduced in FS numerical simulations (Blanco-Cano et al, 2006Omidi et al, 2002Omidi et al, , 2005Strumik et al, 2015) or in a global hybrid Vlasov code (Palmroth et al, 2015). We should also note that observed wave properties have also been reproduced in FS numerical simulations (Blanco-Cano et al, 2006Omidi et al, 2002Omidi et al, , 2005Strumik et al, 2015) or in a global hybrid Vlasov code (Palmroth et al, 2015).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The majority of the ULF waves are either Alfvénic (mostly transverse) or magnetosonic-whistler (mostly compressive). We should also note that observed wave properties have also been reproduced in FS numerical simulations (Blanco-Cano et al, 2006Omidi et al, 2002Omidi et al, , 2005Strumik et al, 2015) or in a global hybrid Vlasov code (Palmroth et al, 2015). We should also note that observed wave properties have also been reproduced in FS numerical simulations (Blanco-Cano et al, 2006Omidi et al, 2002Omidi et al, , 2005Strumik et al, 2015) or in a global hybrid Vlasov code (Palmroth et al, 2015).…”
Section: Introductionmentioning
confidence: 65%
“…Hoppe et al (1981) and Hoppe and Russell (1983) identified them as right-hand polarized in the plasma rest frame. The waves are referred either as almost sinusoidal structures or as more compressional and obliquely propagating waves (Hoppe & Russell, 1983) with an alternative interpretation that the oblique waves can represent a kinetic fast magnetosonic wave resulting from an ion/ion cyclotron right-hand resonant instability (Blanco-Cano & Schwartz, 1997;Gary et al, 1981;Gary, 1991Gary, , 1993Strumik et al, 2015). The waves are referred either as almost sinusoidal structures or as more compressional and obliquely propagating waves (Hoppe & Russell, 1983) with an alternative interpretation that the oblique waves can represent a kinetic fast magnetosonic wave resulting from an ion/ion cyclotron right-hand resonant instability (Blanco-Cano & Schwartz, 1997;Gary et al, 1981;Gary, 1991Gary, , 1993Strumik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These instabilities can generate waves in the upstream region (e.g. Blanco-Cano et al 2011;Wang et al 2015;Strumik et al 2015), so that an increased level A&A 592, A118 (2016) of fluctuations is expected before and after the shocks associated with ICMEs.…”
Section: Introductionmentioning
confidence: 99%
“…A determination of their polarization in the plasma frame is difficult because only single-point measurements are available. Taken into account the compressive nature of the observed waves (Figure 4i) and the propagation angle, we can probably attribute them to the kinetic fast magnetosonic waves (Strumik et al, 2015;Wilson, 2016).…”
Section: Wave Propertiesmentioning
confidence: 81%
“…As a result, ULF wave activity is not detected at the ion foreshock boundary but at another boundary located further downstream, identified as the ULF foreshock boundary (Greenstadt et al, 1980). The wave activity observed in these regions includes quasi-monochromatic waves and occasionally contains a broad spectrum of turbulent electromagnetic fluctuations (for details of wave properties see, e.g., the following papers: Thomsen (1985), Eastwood et al (2005), Narita et al (2006), Burgess et al (2012), Stasiewicz et al (2013), Selzer et al (2014), Strumik et al (2015), Wilson (2016)). Omidi et al (2005) and Blanco-Cano et al (2006) studied the morphology of the foreshock and characterized the nature of ULF waves using global 2-D hybrid simulations.…”
Section: Introductionmentioning
confidence: 99%